Incredible and Shining India - Danish Javed (2025)
India, one of the oldest civilisations, is a constitutionally secular country and the largest democracy in the world. Today, the country finds itself grappling with growing religious intolerance and human rights violations under the Hindutva-influenced Modi-led regime. The religious-racial supremacist policies, mob lynching and brutal gang rapes in the name of religion and caste or otherwise are making recurrent headlines.
Include Ccolour illustration
Keywords: Asian Politics -- India History